2016
DOI: 10.4028/www.scientific.net/msf.879.256
|View full text |Cite
|
Sign up to set email alerts
|

Phase Constitution and Martensitic Transformation Behavior of Au-51Ti-18Co Biomedical Shape Memory Alloy Heat-Treated at 1173K to 1373K

Abstract: Phase constitution and martensitic transformation behavior were investigated for a Au–51Ti–18Co alloy heat-treated at 1173 K to 1373 K for 3.6 ks. The Au–51Ti–18Co alloy was fabricated by Ar arc-melting technique and subsequently by hot-forging at 1423 K for 10.8 ks. X-ray diffraction analysis revealed that B2 parent phase, B19 martensite phase and AuTi3 simultaneously appeared regardless of the heat-treatment temperatures. By increasing the heat-treatment temperature, the volume fraction of AuTi3 was slightly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…It was found that the CSS was slightly decreased with increasing heat-treatment temperature in this experimental range, even though there is small deviation in the results of HT1373. It can be understood that, the reduction in the CSS is majorly caused from the decrease in amount of precipitates which already reported in the references [1][2]. Fig.…”
Section: Resultssupporting
confidence: 58%
See 3 more Smart Citations
“…It was found that the CSS was slightly decreased with increasing heat-treatment temperature in this experimental range, even though there is small deviation in the results of HT1373. It can be understood that, the reduction in the CSS is majorly caused from the decrease in amount of precipitates which already reported in the references [1][2]. Fig.…”
Section: Resultssupporting
confidence: 58%
“…In the other words, the SIMT increased with decreasing the M s of the specimen when the testing temperature is kept constant at room temperature. It has been reported that the M s was slightly increased in the higher heat-treatment conditions in the Au-51Ti-18Co alloy [1][2], the reduction in the σ 0.2 is understandable.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…Au-based biomedical [12][13][14][15] Ni-Ti-based medical instruments (medical implants, 16 stent, 17 orthodontics, 18 surgery, 19 rehabilitation devices 20 ), Aerospace devices (rotary actuators, 21 solar sail, 22 morphing wing 23 ) Cu-based 24 pipe couplings, 25 hydraulic fittings, 26 mechanical dampers, 27,28 energy dissipation devices, 29 textiles 30 Fe-based 31 fishplates for crane rails, 32 pipe couplings, 25 civil structures 33 (concrete reinforcement, 34 damping, 35 pre-stressing elements 36 ) aerodynamic devices. In particular, it can be noted that most of the devices are dealing with aircraft components, with specific regard to wings, and focusing on design, fabrication, testing and modeling aspects.…”
Section: Alloy Applicationmentioning
confidence: 99%